Trace elements and nutrients adsorption onto nano-maghemite in a contaminated-soil solution: A geochemical/statistical approach - Martínez-Fernández, Domingo; Bingöl, Deniz; Komárek, Michael (Journal of hazardous materials, 2014)
Two experiments were carried out to study the competition for adsorption between trace elements (TEs) and nutrients following the application of nano-maghemite (NM) (iron nano-oxide; Fe2O3) to a soil solution (the 0.01molL(-1) CaCl2 extract of a TEs-contaminated soil). In the first, the nutrients K, N, and P were added to create a set of combinations: potential availability of TEs during their interaction with NM and nutrients were studied. In the second, response surface methodology was used to develop predictive models by central composite design (CCD) for competition between TEs and the nutrients K and N for adsorption onto NM. The addition of NM to the soil solution reduced specifically the concentrations of available As and Cd, but the TE-adsorption capacity of NM decreased as the P concentration increased. The CCD provided more concise and valuable information, appropriate to estimate the behavior of NM sequestering TEs: according to the suggested models, K(+) and NH4(+) were important factors for Ca, Fe, Mg, Mn, Na, and Zn adsorption (Radj(2)=95%, except for Zn with Radj(2)=87%). The obtained information and models can be used to predict the effectiveness of NM for the stabilization of TEs, crucial during the phytoremediation of contaminated soils.
Keywords: nanostruktury; železité sloučeniny; Soil Pollutants; látky znečišťující půdu; Nano-oxides; Ferric Compounds; Adsorption; Phosphorus; stopové prvky; adsorpce; Availability; Nanostructures; Nitrogen; Potassium; Trace Elements